Three Components Seismogram Analysis of Tasikmalaya, Indonesia on September 2nd 2009 Earthquake to Investigate the Coulomb Stress Change and Seismicity Rate Change - Madlazim Madlazim; Bagus Jaya Santosa; Widya Utama (Indonesian Journal of Physics, 2010)
During the past decade remarkable progress has been made in studies related to fault interactions and how the occurrence of an earthquake perturbs the stress field in its neighbourhood, which may trigger aftershocks and seismicity rate change. An earthquake event in Tasikmalaya, Indonesia on September 2nd, 2009 at 07:55:02.5 UTC (Universal Time Coordinate), has been investigated to estimate source parameters of the earthquake. Seismogram data was taken from five stations in the vicinity of the epicenter, which have distances less than 15º. All data analyzed are waveforms of three components. Method to estimate the source parameters is combination between iterative deconvolution and discrete wave number (DWN) for local data. The results show that variance reduction between the observed seismogram and the synthetic one and reduced variances for all stations is 61.66%. It indicates that results of the estimation (hypocenter, moment seismic, moment tensor and rupture direction) are suitable to describe source earthquake point. The source parameters of this event are hypocenter (-7.84ο, 107.84ο, 55 km), moment seismic is 4.001e+19 Nm, moment tensor and rupture direction that can describe the focal mechanism of the earthquake. By trial and error we find that a rupture area of 27.20 km x 15.5 km having updip and downdip edges at depths of 0 and 11.7 km respectively, provides a good correlation between zone of increasing Coulomb stress, the three aftershocks hypocentres and zone of increasing seimicity rate.